Does green finance promote enterprises’ green technology innovation in China? - Jiang, Shuangshuang; Liu, Xiaojiao; Liu, Zhonglu; Shi, Hao; Xu, Hongdi (Frontiers in Environmental Science, 2022)
In the carbon neutrality strategy, understanding the effects of green finance on green technology innovation is conductive to promoting the green transformation of the economy. Based on the micro-level and provincial panel data of Shanghai and Shenzhen A-share listed companies from 2012- 2019, this paper explores the impact of green financial development on the enterprises’ green technology innovation. Meanwhile, a mediating effect model and moderating effect model are employed to explore the impact mechanism of green finance on green technological innovation. It was found that green finance significantly improves the enterprises’ green technology innovation, despite sufficient incentives for “quantity” and relatively insufficient motivation for “quality”. The mechanism test found that the green finance encourages enterprises to improve green technology innovation by alleviating corporate financing constraints. The green innovation effect of green finance has gradually increased as regional intellectual property protection improves. The heterogeneity test found that the incentive effect of green financial development on green technology innovation is more evident in state-owned enterprises, enterprises with good internal control quality, and enterprises in the growth period. If only enterprises in the recession stage receive green financial support, a “green innovation bubble” happens. The research conclusions enrich the research on the driving factors of enterprise green innovation, and provide empirical evidence for enhancing the competitiveness of enterprise green innovation and achieving and carbon neutrality.